Revisiting the Ulahingan Epic of the Livunganen-Arumanen Manobos - Cleope, Earl Jude Paul L. (Silliman Journal, 2022)
This paper revisits the trailblazing research on the Ulahingan epic of the Livunganen-Arumanen Manobos spearheaded by the late Dr. Elena G. Maquiso in 1963. In particular, the paper focuses on one of the numerous unpublished manuscripts of the Ulahingan epic, the kepu'unpu'un. Scheduled for publication as Series 6, this transcribed version of the original translation of the epic recounts the migration of Agyu and his clan and their ordeals. In attempting to provide an update on the succeeding initiatives to continue the Ulahingan Research Project after the demise of Dr. Maquiso, this paper aims to draw the attention of folklore scholars and students to this unique Filipino cultural heritage.